A Review of the Research Progress on Optical Fiber Sensors Based on C-Type Structures - Zhijun Gao; Zhenbo Li; Yu Ying (Photonics, 2025)
With the continuous advancement of optical fiber micromachining technology, C-type optical fibers have demonstrated significant potential in the field of optical fiber sensing. By partially or completely removing specific regions of the cladding, a “leakage window” is created, enabling interaction between the optical field and external substances. This structure has facilitated the development of various sensors. This paper reviews recent progress in the research and applications of C-type optical fibers in optical sensing. Based on sensing principles and application scenarios, C-type optical fiber sensors can be categorized into two main types: interferometric and photonic crystal types. This article discusses the fundamental operating principles and structural characteristics of each type, and provides a detailed comparison of their respective advantages and disadvantages. Studies have shown that sensors based on C-type fiber structures offer notable benefits such as simple fabrication, excellent mechanical performance, strong anti-interference capability, and high sensitivity. Therefore, they hold great promise for applications in intelligent monitoring, environmental detection, and healthcare. Finally, this review outlines future research directions for C-type fiber sensors. As technology continues to evolve, future studies are expected to focus on improving sensor stability, expanding application scenarios, and addressing challenges in current fabrication techniques.